Effects of Paretic Single Limb Exercise on Vascular Characteristics Changing of Bilateral Femoral Arteries on Sub Acute Stroke Patients - Wiwiet Irmayanti; Novitri Novitri; Dian M Sari (Journal of Medicine and Health, 2019)
After a stroke, individuals have weakness and decrease mobility of the hemiparetic side, which demands less muscle oxygen consumption; thus, blood flow decrease. It interferes the hemodynamic system include vascular characteristics.The single limb (quadriceps) exercise intervention was aerobic training that focused only on the hemiparetic limb. The aims of this study was to determine the effects of the single limb exercise on vascular characteristics of both side femoral arteries using pre and post-interventional study. Twelve participants in subacute phase of stroke, performed endurance exercise using N-K table on the hemiparetic leg three times a week for eightweeks. The diameter, peak systolic velocity (PSV), total average maximal velocity (TA Max) of both side femoral arteries were measured. We found that the changing of vascular characteristics outcomes on both side femoral arteries were not statistically significant increased. Others factors that may impede vascular characteristics in both femoral arteries were blood viscosity, aging process and periods of exercise. Keywords: femoral arteries, paretic, stroke, vascular characteristics